A 2.45 GHz Semi-Flexible wearable antenna for industrial, scientific and medical band applications - S. M. Shah; N. F. A. Kadir; Z. Z. Abidin; F. C. Seman; S. A. Hamzah; N. Katiran (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
In this work, a compact size, wearable microstrip patch antenna is designed, simulated and fabricated for the Industrial, Scientific and Medical (ISM) band applications with the operating frequency at 2.45 GHz. A semi-flexible substrate material which is Rogers Duroid RO3003™ with a relative dielectric constant, ε_r of 3, loss tangent, tan δ of 0.010 and thickness, h of 1.52 mm has been proposed to ensure it can be worn on clothes. The antenna has a low-profile feature with 24 × 28 mm2 in dimension. Investigation of the antenna under bending condition on the approximate human arm size is also performed and analysed to ensure that the wearable antenna is applicable for on-body. The bending investigation shows that the initial resonant frequency of 2.45 GHz is shifted to 2.3 GHz. However, the reflection coefficient at 2.45 GHz is still greater than the -10-dB which implies that the antenna is still functional at that particular frequency. The Specific Absorption Rate (SAR) of the antenna has also been simulated to examine whether the antenna obeys the SAR limits under the FCC and CNIRP guidelines. The SAR values obtained show that the antenna obeys the standard for 1 mW input power. The SAR value for 1g of human tissue is computed at 0.03999 W/kg (FCC standard: 1.6 W/kg) while for 10g is at 0.01936W/kg (CNIRP standard: 2 W/kg).